Validation of cell-cycle arrest biomarkers for acute kidney injury after pediatric cardiac surgery. - Melanie Meersch (PLoS ONE, 2014)
The lack of early biomarkers for acute kidney injury (AKI) seriously inhibits the initiation of preventive and therapeutic measures for this syndrome in a timely manner. We tested the hypothesis that insulin-like growth factor-binding protein 7 (IGFBP7) and tissue inhibitor of metalloproteinases-2 (TIMP-2), both inducers of G1 cell cycle arrest, function as early biomarkers for AKI after congenital heart surgery with cardiopulmonary bypass (CPB).We prospectively studied 51 children undergoing cardiac surgery with CPB. Serial urine samples were analyzed for [TIMP-2]•[IGFBP7]. The primary outcome measure was AKI defined by the pRIFLE criteria within 72 hours after surgery.12 children (24%) developed AKI within 1.67 (SE 0.3) days after surgery. Children who developed AKI after cardiac surgery had a significant higher urinary [TIMP-2]•[IGFBP7] as early as 4 h after the procedure, compared to children who did not develop AKI (mean of 1.93 ((ng/ml)²/1000) (SE 0.4) vs 0.47 ((ng/ml)²/1000) (SE 0.1), respectively; p<0.05). Urinary [TIMP-2]•[IGFBP7] 4 hours following surgery demonstrated an area under the receiver-operating characteristic curve of 0.85. Sensitivity was 0.83, and specificity was 0.77 for a cutoff value of 0.70 ((ng/ml)²/1000).Urinary [TIMP-2]•[IGFBP7] represent sensitive, specific, and highly predictive early biomarkers for AKI after surgery for congenital heart disease.www.germanctr.de/, DRKS00005062.